THE DEVELOPMENT OF SUSTER SCHOOLS IN PONTIANAK AS A SOCIAL-EDUCATIONAL INSTITUTION IN THE POST-INDEPENDENCE ERA (1951–1985) : Perkembangan Persekolahan Suster Pontianak Sebagai Lembaga Sosial Pendidikan Pasca Kemerdekaan (1951–1985) - Angela Windi Djaskiandini; Astrini Eka Putri; Mohammad Rikaz Prabowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the development of Persekolahan Suster Pontianak as a social educational institution in post-independence Indonesia during the period 1951–1985. The study is grounded in the recognition of education as a strategic sector in national development, as well as the significant role of religious-based educational institutions in expanding access to education, particularly in regional contexts. This research employs a historical method, encompassing heuristics, verification, interpretation, and historiography, utilizing primary sources such as school archives and interviews, alongside secondary sources including scholarly books and journal articles.The findings indicate that Persekolahan Suster Pontianak, managed by the SFIC Susters, evolved from an early caregiving institution into a formal educational establishment in the early twentieth century. Following its closure during World War II, the institution resumed operations in 1951 under the Yayasan Pengabdi untuk Sesama Manusia (YPSM) and successfully adapted to national education policies through the implementation of the national curriculum, the use of Indonesian as the medium of instruction, and structural adjustments in its educational system. Furthermore, the institution functioned as a social agent, contributing to students’ moral, spiritual, and character formation while simultaneously expanding educational access for the local community.